Behavioural response of alate Aphis craccivora Koch (Homoptera: Aphididae) to volatiles from different cowpea cultivars - Diabate, S.; Deletre, E.; Murungi, L.K.; Fiaboe, K.K.M.; Wesonga, J.; Martin, T. (Wiley, 2019)
The cowpea aphid, Aphis craccivora, is a major insect pest of cowpea in Africa. Volatile organic compounds (VOCs) mediate plant–arthropod interactions that could be used in the management of insect pests. In this study, we established the VOC profile involved in the interaction between A. craccivora and four cowpea cultivars, namely Ex‐Luanda, Katumani 80, Machakos 66 and Ken Kunde 1. Behavioural assays were conducted to study host preference and gas chromatography‐mass spectrometry (GC/MS) for chemical analysis of volatiles. In preference assays, alate A. craccivora had no significant preference for any of the four cowpea cultivars tested. However, in the olfactometer assays, the aphids showed a significant preference for odours from cultivar Ex‐Luanda compared to Katumani 80. Machakos 66 and Ken Kunde 1 elicited neutral responses. In pairwise comparisons, alate A. craccivora did not distinguish between odours of respective cowpea cultivars. GC/MS analysis identified 23 compounds in the volatiles of the four cowpea cultivars. Not all compounds were detected in all cowpea cultivars, and the detected compounds amounts varied in each cultivar. Of these, only four compounds (hexanal, (E)‐2‐hexenal, 1‐octen‐3‐ol and p‐xylene) were emitted in significantly different quantities in the four cultivars. A blend of hexanal and (E)‐2‐hexenal added to cowpea cultivar Ex‐Luanda decreased its attractiveness to A. craccivora compared to the control. Our findings showed differential attractiveness of VOCs of cowpea cultivars to A. craccivora, suggesting that VOCs could be used in the management of A. craccivora.